Vitamin D Status During Pregnancy and Risk of Multiple Sclerosis in Offspring of Women in the Finnish Maternity Cohort - Kassandra L. Munger; Julia Åivo; Kira Hongell; Merja Soilu-Hänninen; Heljä-Marja Surcel; Alberto Ascherio (American Medical Association, 2025)
IMPORTANCE Vitamin D has been associated with a decreased risk of multiple sclerosis (MS)
in adulthood; however, some, but not all, previous studies have suggested that in utero
vitamin D exposure may be a risk factor forMS later in life.
OBJECTIVE To examine whether serum 25-hydroxyvitamin D (25[OH]D) levels in early
pregnancy are associated with risk of MS in offspring.
DESIGN, SETTING, AND PARTICIPANTS Prospective, nested case-control study in the Finnish
Maternity Cohort conducted in May 2011.We identified 193 individuals with a diagnosis of MS
before December 31, 2009, whose mothers are in the Finnish Maternity Cohort and had an
available serum sample from the pregnancy with the affected child.We matched 176 cases
with 326 controls on region of birth in Finland, date of maternal serum sample collection,
date of mother’s birth, and date of child’s birth.
MAIN OUTCOMES AND MEASURES Maternal serum 25(OH)D levelswere measured using a
chemiluminescence assay. The risk of MS among offspring and association with maternal
25(OH)D levels were the main outcomes. Conditional logistic regression was used and further
adjusted for sex of the child, gestational age at the time of sample collection, and season of
sample collection to estimate the relative risks and 95%CIs.
RESULTS Of the 193 cases in the study, 163 were female. Of the 331 controls in the study,
218 were female. Seventy percent of serum samples were collected during the first trimester
of pregnancy. The mean (SD) maternal vitamin D levels were in the insufficient vitamin D
range, but higher in maternal control than case samples (15.02 [6.41] ng/mL vs 13.86 [5.49]
ng/mL [to convert to nanomoles per liter, multiply by 2.496]). Maternal vitamin D deficiency
(25[OH]D levels <12.02 ng/mL) during early pregnancy was associated with a nearly 2-fold
increased risk of MS in the offspring (relative risk, 1.90; 95%CI, 1.20-3.01; P = .006)
compared with women who did not have deficient 25(OH)D levels. There was no statistically
significant association between the risk of MS and increasing serum 25(OH)D levels (P = .12).
CONCLUSIONS AND RELEVANCE Insufficient maternal 25(OH)D during pregnancymay
increase the risk of MS in offspring